2004
DOI: 10.1099/mic.0.26797-0
|View full text |Cite
|
Sign up to set email alerts
|

Molecular identification of Vibrio harveyi-related isolates associated with diseased aquatic organisms

Abstract: Fifty strains belonging to Vibrio harveyi, Vibrio campbellii, and the recently described Vibrio rotiferianus, were analysed using phenotypic and genomic techniques with the aim of analysing the usefulness of the different techniques for the identification of V. harveyi-related species. The species V. harveyi and V. campbellii were phenotypically indistinguishable by more than 100 phenotypic features. Thirty-nine experimental strains were phenotypically identified as V. harveyi, but FAFLP, REP-PCR, IGS-PCR and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
157
0
3

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 188 publications
(166 citation statements)
references
References 43 publications
6
157
0
3
Order By: Relevance
“…In recent years, sequencing and comparison of the 16S rRNA gene has become an important tool for identification of bacterial species (Greenwood et al, 2005). However, V. harveyi and V. campbellii share more than 97 % similarity in their 16S rRNA gene sequences and show a 69 % match in DNA-DNA hybridization (Gomez-Gil et al, 2004). Further, the wellstudied V. harveyi strain BB120 was recently proved to be V. campbellii by microarray-based comparative genomic hybridization (Lin et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, sequencing and comparison of the 16S rRNA gene has become an important tool for identification of bacterial species (Greenwood et al, 2005). However, V. harveyi and V. campbellii share more than 97 % similarity in their 16S rRNA gene sequences and show a 69 % match in DNA-DNA hybridization (Gomez-Gil et al, 2004). Further, the wellstudied V. harveyi strain BB120 was recently proved to be V. campbellii by microarray-based comparative genomic hybridization (Lin et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Its fisheries have been performed mainly in the East Sea over several decades [7]. Vibrio (V.) harveyi belonging to the genus Vibrio has been reported to infect a wide range of marine organisms worldwide including fish and invertebrates [1,3,6]. The disease can cause mass mortalities in aquaculture species with significant economic impact.…”
mentioning
confidence: 99%
“…In the family Vibrionaceae, sequence similarities for the 16S rRNA gene are ≥ 97.6% among members of the so-called Vibrio core group, which is formed by 6 species, V. harveyi, V. campbellii, V. ro ti ferianus, V. parahaemolyticus, V. algino ly ticus and V. natriegens (Dorsch et al 1992). Recent studies have shown that the 16S rRNA gene is not adequate for resolution of the 6 species of the core group of the genus Vibrio, because the overlap between the intraspecific and interspecific distances is very large (Gomez-Gil et al 2004, Lin et al 2010, Pascual et al 2010. The phylogenetic analysis of the 16S rRNA gene of strain AP37 also confirms this conclusion.…”
Section: Discussionmentioning
confidence: 99%